Rodent sociality and parasite diversity - Bordes, Frédéric (The Royal Society, 2007)
The risk of parasitism is considered to be a general cost of sociality and individuals living in larger groups are typically considered to be more likely to be infected with parasites. However, contradictory results have been reported for the relationship between group size and infection by directly transmitted parasites. We used independent contrasts to examine the relationship between an index of sociality in rodents and the diversity of their macroparasites (helminths and arthropods such as fleas, ticks, suckling lice and mesostigmatid mites). We found that the species richness of directly transmitted ectoparasites, but not endoparasites, decreased significantly with the level of rodent sociality. A greater homogeneity in the biotic environment (i.e. a reduced number of cohabiting host species) of the more social species may have reduced ectoparasites' diversity by impairing ectoparasites transmission and exchange. Our finding may also result from beneficial outcomes of social living that include behavioural defences, like allogrooming, and the increased avoidance of parasites through dilution effects.